2020
DOI: 10.1042/bsr20200092
|View full text |Cite
|
Sign up to set email alerts
|

CTRP3 ameliorates cerulein-induced severe acute pancreatitis in mice via SIRT1/NF-κB/p53 axis

Abstract: Severe acute pancreatitis (SAP) is a common and life-threatening clinical acute abdominal disease. C1q/tumor necrosis factor-related protein 3 (CTRP3), a novel paralog of adiponectin, has been identified as a crucial regulator in multiple types of inflammatory disorders. However, the biological role of CTRP3 in SAP remains poorly understood. This study aimed to characterize the role of CTRP3 in SAP and illuminate the potential mechanisms involved. In the current study, SAP mouse models were induced by seven ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…We have already shown that CTRP3 ameliorates development of autoimmune arthritis (21). Furthermore, CTRP3 is implicated in the regulation of myocardiac dysfunction, inflammatory bowel disease, severe acute pancreatitis and chronic kidney diseases (21)(22)(23)(24)(25). Because involvement of Th17 cells is suggested in these diseases (72)(73)(74)(75), it is possible that CTRP3 regulates excess inflammation in these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already shown that CTRP3 ameliorates development of autoimmune arthritis (21). Furthermore, CTRP3 is implicated in the regulation of myocardiac dysfunction, inflammatory bowel disease, severe acute pancreatitis and chronic kidney diseases (21)(22)(23)(24)(25). Because involvement of Th17 cells is suggested in these diseases (72)(73)(74)(75), it is possible that CTRP3 regulates excess inflammation in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…CTRP3 is implicated in the development of myocardiac dysfunction, inflammatory bowel diseases, severe acute pancreatitis and chronic kidney diseases (22)(23)(24)(25). CTRP3 also functions as an antagonist for LPS, and modulates antiinflammatory functions of monocytes, macrophages, adipocytes and fibroblasts (26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been reported that p53 acetylation could be capable of suppressing cell proliferation and survival, which would contribute to development of AP [29] . Related research has suggested that the activation of SIRT1 could inhibit the acetylation of p53 and repress the apoptosis of acinar cells, thus to alleviate the SAP model induced by caerulein [30] . In addition, another study indicated that resveratrol (SIRT1 activator) signi cantly reduced the severity of AP, effectively improved the survival rate, relieved the in ammatory response and decreased the acinar necrosis and apoptosis in a mouse model of L-arginine-induced acute necrotizing pancreatitis, which might be related to the enhancement of SIRT1-mediated deacetylation of p53 [27] .…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the receptor-interacting protein kinase 1(RIPK1)/NF-κB/aquaporin 8 (AQP8) axis might serve as a potential regulatory pathway to inhibit acinar cell necrosis in early acute pancreatitis (Duan et al., 2019 ). The latest study proved that C1q/tumor necrosis factor-related protein 3 (CTRP3) exerted protective effects in acute pancreatitis via suppressing silent information regulator 1 (SIRT1)/NF-κB/p53 axis (Lv et al., 2020 ).…”
Section: Molecular and Cellular Mechanisms Of Acute Pancreatitismentioning
confidence: 99%